Pengaruh Pengungkapan Corporate Social Responsibility dan Good Corporate Governance terhadap Profitabilitas Perusahaan Indeks Sri Kehati - Syahrul Effendi (Jurnal Ekonomi, 2018)
The purpose of this study was to examine the effect of disclosure of Corporate Social Responsibility and Good Corporate Governance to the profitability of a company incorporated in sri kehati index in the Indonesia Stock Exchange in the period 2011-2015. This research is a correlation regression testing as an article describing the phenomenon in the form of the relationship between variables. The research data was obtained from annual reports and financial sites Indonesia Stock Exchange (BEI). Samples used as many as 14 companies qualified financial reports, sustainability reports listed in Indonesia Stock Exchange in 2011-2015. The sampling technique used literature. This study uses multiple regression analysis. Based on the analysis it can be concluded that the disclosure of Corporate Social Responsibility positive effect on NPM. Good Corporate Governance (Size commissioners) positive effect on ROE, ROA. Good Corporate Governance (Independent Commissioner) no positive effect on ROA and NPM. Good Corporate Governance (Audit Committee) positive effect on ROA and ROE.